MANAGEMENT OF MEGACOLON CASES IN CATS WITH THE ADDITION OF YELLOW PUMPKIN TO THEIR FEED: A CASE REPORT - I Putu Indra Manik Pradipta; Putu Devi Jayanti; I Gede Soma; I Wayan Nico Fajar Gunawan (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Megacolon is a pathological condition associated with failure to defecate normally, most commonly diagnosed in cats. The medical management of megacolon has not been widely reported, hence the importance of writing this article. This case study is about a 2-year-old male Angora cat who was observed to have difficulty in defecating since 3 weeks. Clinical examination revealed normal borborygmus sounds and a solid abdominal consistency suspected to be fecal accumulation. Hematology examination was performed and the result showed Neutrophilia. Radiological examination showed accumulation of hardened feces in the colon. Based on the history, clinical examination, and supporting examination, the animal had megacolon with a prognosis of fausta. The cat was given lactulose and a feed mixture of wet food and pumpkin supplement. Results from laxative therapy with pumpkin supplementation for seven days showed the cat's fecal consistency FCS 3.5. The owner is advised to change the cat's feed to wet food with pumpkin added, as well as perform physical exercise on the cat.